2015
DOI: 10.1016/j.endm.2015.06.049
|View full text |Cite
|
Sign up to set email alerts
|

On a Ramsey-type problem of Erdős and Pach

Abstract: In this paper we show that there exists a constant C > 0 such that for any graph G on Ck ln k vertices either G or its complement G has an induced subgraph on k vertices with minimum degree at least 1 2 (k − 1). This affirmatively answers a question of Erdős and Pach from 1983.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Erdős and Pach [9] found that the quasi-Ramsey numbers undergo a dramatic change in growth in k in a narrow window around c = 1/2: if c < 1/2 then they have linear growth, while if c > 1/2 they have singly exponential growth. They developed a fairly precise understanding of the transition at the point c = 1/2 -the present authors together with Pach [17] and with Long [15] have recently refined this.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Erdős and Pach [9] found that the quasi-Ramsey numbers undergo a dramatic change in growth in k in a narrow window around c = 1/2: if c < 1/2 then they have linear growth, while if c > 1/2 they have singly exponential growth. They developed a fairly precise understanding of the transition at the point c = 1/2 -the present authors together with Pach [17] and with Long [15] have recently refined this.…”
Section: Introductionmentioning
confidence: 78%
“…Here we give a proof of Theorem 1 and discuss some consequences of it. Our proof of Theorem 1 is based on the proof of [15,Theorem 2], which in turn is inspired by a method of Erdős and Pach [9].…”
Section: Multi-colour Quasi-ramsey Results For Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…(k) = Ω k (k−1) (k) = O(k 2 ),but what is the correct behaviour of R * (k−1) (k)? Note added: subsequent to the present work, three of the authors have improved the upper bound to O(k ln 2 k)[11].…”
mentioning
confidence: 90%